An unusual cause of epigastric pain and diaphoresis - Vivian Georgopoulou; Evgenia Gouridou; Athina Pyrpasopoulou; Andreana Kozanidou; Christodoulos Papadopoulos; Stergios Tzikas; Maria Sidiropoulou (Heliyon, 2020)
The median arcuate ligament, or celiac artery compression syndrome is a rare syndrome, caused by extrinsic compression of the celiac trunk by the median arcuate ligament. Its symptomatology mainly comprises of visceral angina. Differential diagnosis includes cardiovascular angina, other vascular events and causes of vagotonia. The case reported here refers to a middle aged male patient who presented with intermittent epigastric pain and diaphoresis after a long drive. Diagnosis was made radiologically, during computed tomography scan angiography, which revealed a hook-like appearance of the celiac artery partially loosened during inspiration. Careful history and cautious reviewing of the imaging may refrain from further, unnecessary, diagnostic investigations.